Edytorstwo muzyczne w Krakowie w latach 1850-1918 - Lewicki, Michał (Wydawnictwo Księgarnia Akademicka, 2022)
The thesis deals with the activity and the output of music publishers active in Krakow in years 1850–1918, with regard to 40 institutions. The work was divided into three parts and twelve chapters, with an appendix. The first part contains an overview of Krakow’s music publishers and describes the extent of their activities. Production, distribution and advertising of musical prints was characterised by following criteria: editorial form and graphic design, relations composer-editor, accommodation of a musical manuscript for printing, printing techniques, print run size, sheet music vending, activity of sheet music lending libraries, ways and forms to disseminate information on sheet music publishing. The second part contains multi-aspect analysis of the music repertoire published in Krakow. The following aspects were characterised: composers, dedicatees, performing cast members and musical genres. Songbooks and instrumental methods were given a separate insight. The third part presents the role of Krakow’s music publishing in a music life of Krakow. The examples for the presence of published sheet music in programs of contemporary concerts and in scholarly practice were given and commented. This part characterises a publishers’ role in the propagation of wide-ranged composers’ output; Krakow’s music publishers were assessed and confronted with other publishing centres. The appendix contains a detailed catalogue of 1735 Krakow’s musical publications from years 1850–1918, that together with 109 Stichvorlage manuscripts and other manuscripts as well as prints constitute a source documentation for the dissertation.